Carotenoid bioaccessibility in pulp and fresh juice from carotenoid-rich sweet oranges and mandarins1. Issue 6 (10th June 2015) - Rodrigo, María Jesús; Cilla, Antonio; Barberá, Reyes; Zacarías, Lorenzo
<x xml:space="preserve">Abstract</x> In this work the concentration and bioaccessibility of carotenoids in sweet oranges and mandarins rich in bioactive carotenoids were evaluated in pulp and fresh juice.